Clinical and Urodynamic Evaluation of Filling Phase in Type 2 Diabetic Patients (Iraqi Journal of Medical Sciences, 2024)
Background: Type 2 diabetes mellitus (T2DM) causes multiple complications in various body systems.Objective: To look into the effect of the duration of T2DM on the filling phase of the urination process. Methods: One hundred and twenty patients with T2DM and filling (storage) symptoms participated in this cross-sectional study. Each patient\'s full history was recorded. A full urodynamic test was done. According to T2DM duration, participants were categorized into two groups; short duration (1-10 years) and long duration (>10 years). The patients answered the questionnaire about their symptoms (nocturia, frequency, urge incontinence, and urgency). Then the patients underwent a full urodynamic study and the filling phase parameters were recorded (bladder compliance, bladder capacity, first sensation, normal desire, and strong desire). The association between demographic and clinical parameters and urodynamic study outcomes was investigated.Results: According to subjective symptoms, there was a significant difference between the two groups in term of nocturia (P = 0.001) and no significant difference in other subjective terms. According to urodynamic test findings, there was a significant difference between the two groups in terms of bladder compliance, bladder capacity, first sensation, normal desire, and strong desire (P
Keywords: Urodynamic test; urgency; urge incontinence; frequency; nocturia; bladder compliance; bladder capacity; first sensation; normal desire; strong desire